2022
DOI: 10.1002/imhj.21985
|View full text |Cite
|
Sign up to set email alerts
|

Understanding links between maternal perinatal posttraumatic stress symptoms and infant socioemotional and physical health

Abstract: Maternal posttraumatic stress symptoms (PTSS) are associated with adverse consequences for older children, but very few studies have examined links between perinatal maternal PTSS and infant outcomes. Trauma exposure and psychopathology, including PTSS, is often heightened for women during pregnancy through 1 year postpartum. Therefore, the perinatal period may be a critical time for understanding the risk maternal PTSS and other mental health factors pose to the socioemotional and physical health of infants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Demographics and family socioeconomic adversity Caregivers reported on their child's age, gender, race, and ethnicity, as well as on their own education level, employment status (not employed vs. employed), marital status (single vs. two-parent household), and family income. Consistent with prior research (e.g., Huffhines et al, 2022;Tyrka et al, 2015), indicators of socioeconomic risk (education ≤ high school diploma, nonemployment, single parenthood) were summed to provide a parsimonious assessment of family socioeconomic adversity (possible scores ranged from 0 to 3).…”
Section: Methodsmentioning
confidence: 99%
“…Demographics and family socioeconomic adversity Caregivers reported on their child's age, gender, race, and ethnicity, as well as on their own education level, employment status (not employed vs. employed), marital status (single vs. two-parent household), and family income. Consistent with prior research (e.g., Huffhines et al, 2022;Tyrka et al, 2015), indicators of socioeconomic risk (education ≤ high school diploma, nonemployment, single parenthood) were summed to provide a parsimonious assessment of family socioeconomic adversity (possible scores ranged from 0 to 3).…”
Section: Methodsmentioning
confidence: 99%
“…PPD and PTSD are characterized by a refusal attitude for life and ambivalent behavioral, cognitive, and somatic disorders. In addition to the social and healthcare costs, both mental difficulties entail negative effects on the physical and emotional health of the woman, leading to maladaptation to motherhood and serious misalignments in the affective and physical development of the newborn [22][23][24]. It has been identified that PPD and PTSD can be activated one year after childbirth [18,23].…”
Section: Introductionmentioning
confidence: 99%